Peningkatan Kompetensi SDM melalui Pelatihan Keterampilan Digital bagi UMKM di Yayasan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Endang Kustini; Mukrodi Mukrodi; Rima Handayani (Jurnal PKM Manajemen Bisnis, 2026)
The development of human resources in small and medium enterprises (SMEs) is crucial to enhance productivity, competitiveness, and digital literacy in local communities. Many SMEs still face challenges in adopting digital tools for marketing, financial management, and operational efficiency, which limits their growth potential. The Community Service Program (PKM) entitled “Improving Human Resource Competence through Digital Skills Training for SMEs at Yayasan Tajaul Karomah, Situ Gadung Village, Tangerang Regency” aimed to address these challenges by enhancing digital competencies among educators, administrative staff, and community members. The program was conducted on October 4–5, 2025, at Yayasan Tajaul Karomah and involved three lecturers from Universitas Pamulang as facilitators and 26 participants, including teachers, administrative personnel, and local residents. The PKM activities employed a combination of material presentation, hands-on practice, group discussions, and question-and-answer sessions to ensure interactive learning and skill development. Results of the program indicated significant improvement in participants’ understanding and ability to utilize digital platforms for business operations, including social media marketing, online transaction management, and digital record-keeping. Participants also demonstrated increased confidence, collaboration, and initiative in applying digital solutions to support SME development within their community. The program successfully fostered not only technical skills but also an entrepreneurial mindset aligned with digital transformation needs. These outcomes highlight the effectiveness of participatory and practice-oriented training in strengthening human resource capabilities for local economic empowerment.